2013
DOI: 10.5897/ajpp2013.3754
|View full text |Cite
|
Sign up to set email alerts
|

Substandard rifampicin based anti-tuberculosis drugs common in Ugandan drug market

Abstract: Tuberculosis (TB) is an important curable infectious disease in Uganda; its treatment however is facing a challenge of increasing drug resistance. Although rifampicin containing fixed-dose combination (R-FDC) drugs are a mainstay in TB treatment, about one fifth is reportedly substandard in the global drug market. The aim of this study was to determine the quality of R-FDC and rifampicin single formulation anti-TB drugs in Kampala city, Uganda. Eight private and five public pharmacies were randomly selected, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…sampling strategy has to be followed to collect a large number of units of each drug product, sampled from different points of the supply-chain, to perform all pharmacopoeial tests. Some studies indicated correct quality of the drug products tested although these studies did not follow the recommendations of European or United States Pharmacopeia, because they did not calculate the acceptance value (AV) for uniformity of dosage units, or used an incorrect number of units [6,7]. In this regard, it is very common to find in African research groups studies conducted with the minilab, which is a semi-quantitative technique that is not suitable for the detection of substandard drug products [8].…”
Section: Plos Onementioning
confidence: 99%
“…sampling strategy has to be followed to collect a large number of units of each drug product, sampled from different points of the supply-chain, to perform all pharmacopoeial tests. Some studies indicated correct quality of the drug products tested although these studies did not follow the recommendations of European or United States Pharmacopeia, because they did not calculate the acceptance value (AV) for uniformity of dosage units, or used an incorrect number of units [6,7]. In this regard, it is very common to find in African research groups studies conducted with the minilab, which is a semi-quantitative technique that is not suitable for the detection of substandard drug products [8].…”
Section: Plos Onementioning
confidence: 99%